Electrochemical treatment method for improving corrosion resistance of reinforcing steel bars in concrete by using seawater

By conducting electrodeposition in seawater and deionization in chloride-free water, an inorganic salt-colloid protective layer is formed, which solves the environmental pollution and high cost problems of steel bar corrosion problems in the existing technology, and achieves the improvement of the efficient corrosion resistance of steel bars and low cost operation.

CN119121344APending Publication Date: 2024-12-13ANHUI UNIVERSITY OF ARCHITECTURE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411265228.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Among the existing reinforced concrete protection technology, the problem of steel bar corrosion is particularly prominent, especially in areas containing chloride ions. The existing methods have defects such as environmental pollution, high cost and complex process, and it is difficult to maintain low cost while improving the anti-chlorination performance and Easy to be.

Method used

Electrodeposition is performed by placing the steel bars in seawater and connecting the power source to the anode material to form an inorganic salt-colloid coating, and then removing surface ions in chloride-free water, simplifying the process flow and reducing costs.

Benefits of technology

By forming an efficient inorganic salt-colloid protective layer, the corrosion resistance of the steel bars is significantly improved, the risk of environmental pollution is reduced, and the process is simple and efficient, which is suitable for promotion in marine engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121344A_ABST
    Figure CN119121344A_ABST
Patent Text Reader

Abstract

The invention provides an electrochemical treatment method for improving corrosion resistance of reinforcing steel bars in concrete by using seawater. According to the electrochemical treatment method for improving the corrosion resistance of the reinforcing steel bar in the concrete by using the seawater, the reinforcing steel bar is placed in the seawater, meanwhile, the anode material is placed in the seawater, and the reinforcing steel bar and the anode material are connected with a negative electrode and a positive electrode of a power supply respectively for electro-deposition to form an inorganic salt-colloid coating on the surface of the reinforcing steel bar, so that the self-corrosion potential of the reinforcing steel bar can be improved; the corrosion resistance is improved; after the steel bar is subjected to cathode current electrodeposition treatment, the self-corrosion potential of the steel bar is increased, the corrosion current is reduced, and the corrosion resistance is improved; the seawater solution is easy to obtain, low in cost, free of pollution and suitable for popularization and application, and local materials are convenient to use especially in offshore engineering; the treatment method is simple, convenient and efficient, and can be popularized under general engineering conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of reinforced concrete protection, and in particular to an electrochemical treatment method for improving the corrosion resistance of steel bars in concrete by using seawater. Background Art

[0002] As the most widely used material in civil engineering, reinforced concrete has a vital durability. Steel bar corrosion is the primary reason for the decline in durability of reinforced concrete structures. In this regard, the strategy of "prevention first, prevention and treatment combined" is currently adopted. In many areas containing chloride ions, chloride ion erosion has become a key factor leading to steel bar corrosion. Improving the chloride ion resistance of steel bars in concrete is of great significance. It can ensure structural safety, extend service life, reduce maintenance costs, ensure project quality and sustainable development, and provide strong support for the stability and long-term operation of various infrastructure construction.

[0003] The prior art discloses a method for electrophoretic deposition of graphene coating on a carbon steel substrate. The method first uses concentrated hydrochloric acid to dope graphene nanofragments, and obtains H-doped graphene nanofragments by suction filtration; then the graphene nanofragments are placed in a mixed organic solvent of N-methylpyrrolidone / acetonitrile, and magnetically stirred after ultrasonic treatment to obtain a dispersed graphene colloidal solution; finally, the colloidal solution is used as an electrolyte to deposit the graphene coating on the carbon steel substrate by electrophoretic deposition. However, this method has certain defects. The colloidal solution used is an organic solution, which is easy to cause environmental pollution, and the solution preparation method is complicated and the cost is high.

[0004] The prior art discloses a steel bar corrosion-resistant coating for marine engineering concrete and a preparation method thereof. This method significantly improves the corrosion resistance of the coating by adding self-repairing corrosion microcapsules, metal powder, and graphene oxide powder to the electrophoretic coating, and utilizing the self-repairing property of the self-repairing microcapsules and the combined effect of cathodic protection. This corrosion-resistant coating has excellent adhesion and corrosion resistance, and can extend the service life of the steel bar. However, this method also has shortcomings. The preparation of the colloidal solution is complicated, the use of self-repairing microcapsules increases the application cost, and the complexity of the solution also complicates the construction process during the application process, and does not have the advantages of convenience and low cost.

[0005] In some engineering conditions, such as marine engineering, steel corrosion is usually an important cause of structural degradation. Therefore, many researchers have conducted a lot of research on improving the corrosion resistance of steel bars. However, it should be noted that while improving the corrosion resistance of steel bars, we should also pay attention to the cost of steel bar anti-corrosion and the applicability and convenience of the corresponding methods. This is another important direction for the development of steel bar anti-corrosion technology and methods.

[0006] Based on the defects in the preparation of current steel bar corrosion-resistant coatings, it is necessary to improve this. Summary of the invention

[0007] In view of this, in order to address the above-mentioned deficiencies in the prior art, the present invention provides an electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater, thereby efficiently improving the corrosion resistance of steel bars in concrete in a low-cost manner.

[0008] In order to achieve the above technical objectives, the present invention provides an electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater, comprising the following steps:

[0009] The steel bar is placed in the seawater, and an anode material is placed in the seawater;

[0010] The steel bar and the anode material are connected to the negative electrode and the positive electrode of the power source respectively to perform electrodeposition to form a protective layer on the surface of the steel bar;

[0011] The steel bar after the electrodeposition treatment is taken out and placed in water without chloride ions, and an anode material is placed in the water at the same time, and the steel bar and the anode material are connected to the negative electrode and the positive electrode of the power supply respectively to remove the ions on the surface of the steel bar;

[0012] Remove the steel bars and dry them.

[0013] Preferably, the seawater includes ions of the following concentrations: chloride ions 18995-191452 mg / L, sodium ions 10589-10652 mg / L, sulfate ions 2665-2677 mg / L, magnesium ions 1288-1328 mg / L, calcium ions 411-452 mg / L, potassium ions 398-401 mg / L, and zinc ions 0.024-0.025 mg / L.

[0014] Preferably, the steel bar and the anode material are connected to the negative electrode and the positive electrode of the power supply respectively, and in the step of electrodeposition, the process parameters of the electrodeposition control are: the cathode current density is 0.75-5A / m 2 , the deposition time is 50min~24h, the temperature of the inorganic salt solution is 20~30℃, and the maximum power supply voltage does not exceed 50V.

[0015] Preferably, the steel bar after electrodeposition treatment is taken out and placed in water without chloride ions, and an anode material is placed in the water, and the steel bar and the anode material are connected to the negative electrode and the positive electrode of the power supply respectively to remove the ions on the surface of the steel bar. The process parameters controlled are: the cathode current density is 0.25-2A / m 2 , time is 5 to 30 minutes, and the maximum power supply voltage does not exceed 30V.

[0016] Preferably, before placing the steel bars in the seawater, the method further comprises filtering the seawater to remove suspended matter in the seawater.

[0017] Preferably, before placing the steel bars in seawater, the steel bars are pre-treated, and the pre-treatment includes: degreasing, pickling, water washing, and sandblasting the steel bars in sequence for use.

[0018] Preferably, the oil removal is specifically:

[0019] The steel bar is placed in an alkali solution and ultrasonically treated at 30-50°C;

[0020] And / or, the pickling is specifically:

[0021] The degreased steel bars are immersed in a hydrochloric acid solution with a concentration of 0.1 to 0.2 mol / L for 5 to 20 minutes.

[0022] Preferably, the alkali solution includes at least one of sodium hydroxide solution, sodium carbonate solution, sodium phosphate solution, and sodium silicate solution;

[0023] The mass concentration of the alkali solution is 2 to 10%;

[0024] The ultrasonic treatment time is 10 to 20 minutes;

[0025] Filtering the seawater to remove suspended matter in the seawater specifically includes filtering the seawater using a quartz sand filter, an activated carbon filter, or an ultrafiltration membrane filter.

[0026] Preferably, in the steps of placing the steel bar in seawater, placing the anode material in the seawater, and taking out the steel bar after the electrodeposition treatment and placing it in water without chloride ions, and placing the anode material in the water, the distance between the steel bar and the anode material is 5 to 10 cm;

[0027] The anode material includes at least one of graphite and stainless steel.

[0028] Preferably, in the step of taking out the steel bars and drying them, the drying temperature is 30 to 50° C. and the drying time is 15 to 60 minutes.

[0029] The electrochemical treatment method of the present invention for improving the corrosion resistance of steel bars in concrete by using seawater has the following beneficial effects compared with the prior art:

[0030] The electrochemical treatment method for improving the corrosion resistance of steel bars in concrete by using seawater of the present invention comprises the following steps: placing the steel bars in seawater, placing an anode material in the seawater at the same time, connecting the steel bars and the anode material to the negative electrode and the positive electrode of a power source respectively, and performing electrodeposition to form an inorganic salt-colloid coating on the surface of the steel bars, thereby improving the self-corrosion potential and the corrosion resistance of the steel bars; after the steel bars are subjected to cathode current electrodeposition treatment, the self-corrosion potential thereof increases, the corrosion current decreases, and the corrosion resistance is improved; after electrodeposition in a seawater solution, an inorganic salt-colloid sediment protective layer (mainly magnesium hydroxide, calcium carbonate, zinc oxide inorganic salt substances and metal oxide or hydroxide colloid) is formed on the surface, thereby further improving the corrosion resistance of the steel bars; the seawater solution is easy to obtain, low in cost, pollution-free, and suitable for popularization and use, especially in offshore engineering, where local materials are convenient to obtain; the treatment method of the present invention is simple and efficient, and can be promoted under general engineering conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 The surface morphology of the steel bar before the electrodeposition treatment and after the treatment according to the method of Example 1;

[0033] Figure 2 The surface microstructure of the steel bar that has not been treated with electrodeposition and the steel bar treated according to the method of Example 1 after being placed in a salt spray environment for 7 days;

[0034] Figure 3 is the linear polarization curve of the steel bar before electrodeposition treatment;

[0035] Figure 4 is the linear polarization curve of the steel bar after being treated according to the method in Example 1. DETAILED DESCRIPTION

[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0038] The present application provides an electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater, comprising the following steps:

[0039] S1. placing steel bars in seawater and placing anode materials in the seawater;

[0040] S2, connecting the steel bar and the anode material to the negative electrode and the positive electrode of the power supply respectively, and performing electrodeposition to form a protective layer on the surface of the steel bar;

[0041] S3, taking out the steel bar after the electrodeposition treatment and placing it in water without chloride ions, placing an anode material in the water, and connecting the steel bar and the anode material to the negative electrode and the positive electrode of the power supply respectively to remove ions on the surface of the steel bar;

[0042] S4. Take out the steel bars and dry them.

[0043] The electrochemical treatment method for improving the corrosion resistance of steel bars in concrete by using seawater of the present invention comprises placing the steel bars in seawater, placing anode materials in the seawater at the same time, connecting the steel bars and the anode materials to the negative electrode and the positive electrode of a power source respectively, and performing electrodeposition to form an inorganic salt-colloid coating on the surface of the steel bars, thereby improving the self-corrosion potential and the corrosion resistance thereof. The present invention utilizes seawater, an electric field and an electrochemical reaction to generate an inorganic salt-colloid sediment with high adhesion on the surface of the original smooth steel bars, wherein the inorganic salt-colloid sediment can protect the steel bars and increase their corrosion resistance, and has the characteristics of low cost and simple operation.

[0044] In some embodiments, seawater includes the following concentrations of ions: chloride ions 18995-191452 mg / L, sodium ions 10589-10652 mg / L, sulfate ions 2665-2677 mg / L, magnesium ions 1288-1328 mg / L, calcium ions 411-452 mg / L, potassium ions 398-401 mg / L, and zinc ions 0.024-0.025 mg / L.

[0045] In some embodiments, the steel bar and the anode material are connected to the negative electrode and the positive electrode of the power supply respectively, and in the step of electrodeposition, the process parameters of the electrodeposition control are: the cathode current density is 0.75-5A / m 2 , the deposition time is 50min~24h, the temperature of the inorganic salt solution is 20~30℃, and the maximum power supply voltage does not exceed 50V.

[0046] In some embodiments, the steel bar after electrodeposition treatment is taken out and placed in water without chloride ions, and an anode material is placed in the water, and the steel bar and the anode material are connected to the negative electrode and the positive electrode of the power supply respectively to remove the ions on the surface of the steel bar. The controlled process parameters are: the cathode current density is 0.25-2A / m 2 , time is 5 to 30 minutes, and the maximum power supply voltage does not exceed 30V.

[0047] Specifically, in the above embodiment, the steel bar after the electrodeposition treatment is taken out and placed in water without chloride ions, and electrolysis is performed to remove the remaining chloride ions and sulfate ions on the surface of the steel bar.

[0048] In some embodiments, before placing the steel bars in the seawater, the method further includes filtering the seawater to remove suspended matter in the seawater.

[0049] In some embodiments, before placing the steel bars in seawater, the steel bars are also pre-treated, and the pre-treatment includes: degreasing, pickling, water washing, and sandblasting the steel bars in sequence for use.

[0050] In some embodiments, degreasing is specifically:

[0051] Place the steel bars in an alkali solution and perform ultrasonic treatment at 30-50°C.

[0052] In some embodiments, pickling is specifically:

[0053] The degreased steel bars are immersed in a hydrochloric acid solution with a concentration of 0.1 to 0.2 mol / L for 5 to 20 minutes.

[0054] In some embodiments, the alkali solution includes at least one of a sodium hydroxide solution, a sodium carbonate solution, a sodium phosphate solution, and a sodium silicate solution;

[0055] The mass concentration of the alkali solution is 2 to 10%;

[0056] The ultrasonic treatment time is 10 to 20 minutes;

[0057] In some embodiments, filtering the seawater to remove suspended matter in the seawater specifically comprises filtering the seawater using a quartz sand filter, an activated carbon filter, or an ultrafiltration membrane filter.

[0058] Specifically, in the above embodiment, an activated carbon filter is used to filter seawater impurities, the filtration flow rate is controlled at 15 cubic meters per hour, and the activated carbon filling amount is 50% of the filter volume; the backwash cycle is set to run for 24 hours, and the backwash intensity is achieved by adjusting the water flow rate and pressure. The backwash water flow rate is 20 cubic meters per hour.

[0059] Specifically, in the above embodiment, when a quartz sand filter is used to filter seawater impurities, the filtration flow rate is controlled at 2 cubic meters per hour, the quartz sand filling height is usually 80% of the filter height, and the particle size gradually decreases from the upper layer to the lower layer; the backwash cycle is set to be carried out after 48 hours of operation, and the backwash intensity is controlled by adjusting the water flow rate and pressure, and the backwash water flow rate is 18 cubic meters per hour.

[0060] In some embodiments, the steel bars are placed in seawater, anode materials are placed in the seawater, and the steel bars after electrodeposition treatment are taken out and placed in water without chloride ions, and in the step of placing anode materials in water, the distance between the steel bars and the anode materials is 5 to 10 cm.

[0061] In some embodiments, the anode material includes at least one of graphite and stainless steel.

[0062] In some embodiments, in the step of taking out the steel bars and drying them, the drying temperature is 30-50° C. and the drying time is 15-60 min.

[0063] The following further illustrates the electrochemical treatment method of the present invention for improving the corrosion resistance of steel bars in concrete by using seawater with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0064] Example 1

[0065] This embodiment provides an electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater, comprising the following steps:

[0066] S1. Pre-treat the surface of the steel bar: the steel bar is degreased, pickled, washed, and sandblasted before use; the degreasing step is to ultrasonically clean the steel bar in a sodium hydroxide solution with a mass concentration of 5% for 15 minutes at a degreasing temperature of 30°C; the pickling step is to soak the degreased steel bar in a 0.2 mol / L dilute hydrochloric acid solution for 10 minutes;

[0067] S2, filtering the seawater using an activated carbon filter to remove suspended matter in the seawater;

[0068] The filtered seawater includes the following concentrations of ions: chloride ions 18995mg / L, sodium ions 10589mg / L, sulfate ions 2665mg / L, magnesium ions 1288mg / L, calcium ions 452mg / L, potassium ions 401mg / L, and zinc ions 0.024mg / L;

[0069] S3, cathode electrodeposition: placing the steel bar in seawater from which suspended matter has been removed, placing an anode material in the seawater, connecting the steel bar and the anode material to the negative electrode and the positive electrode of a power source respectively, and performing electrodeposition to form an inorganic salt-colloidal sediment protective layer on the surface of the steel bar;

[0070] The process parameters of electrodeposition control are: cathode current density is 1.0A / m 2 , the deposition time is 50min, the seawater temperature is 25℃, and the power supply voltage is 20V;

[0071] The distance between the steel bar and the anode material is 8 cm;

[0072] The anode material is graphite;

[0073] S4, removing chloride ions: taking out the steel bars after the electrodeposition treatment and placing them in water without chloride ions, placing an anode material in the water, and connecting the steel bars and the anode material to the negative electrode and the positive electrode of the power supply respectively to remove ions on the surface of the steel bars;

[0074] The controlled process parameters are: cathode current density is 0.3A / m 2 , time is 20min, power supply voltage is 20V, distance between steel bar and anode material is 8cm, anode material is graphite;

[0075] S5. Drying: Take out the steel bars and dry them at a drying temperature of 30°C for 20 minutes.

[0076] Example 2

[0077] This embodiment provides an electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater, comprising the following steps:

[0078] S1. Pre-treat the surface of the steel bar: the steel bar is degreased, pickled, washed, and sandblasted before use; the degreasing step is to ultrasonically clean the steel bar in a sodium hydroxide solution with a mass concentration of 5% for 15 minutes at a degreasing temperature of 30°C; the pickling step is to soak the degreased steel bar in a 0.2 mol / L dilute hydrochloric acid solution for 10 minutes;

[0079] S2, filtering the seawater using a quartz sand filter to remove suspended matter in the seawater;

[0080] The filtered seawater includes the following concentrations of ions: chloride ion 191452mg / L, sodium ion 10625mg / L, sulfate ion 2677mg / L, magnesium ion 1328mg / L, calcium ion 411mg / L, potassium ion 398mg / L, zinc ion 0.025mg / L;

[0081] S3, cathode electrodeposition: placing the steel bar in seawater from which suspended matter has been removed, placing an anode material in the seawater, connecting the steel bar and the anode material to the negative electrode and the positive electrode of a power source respectively, and performing electrodeposition to form an inorganic salt-colloidal sediment protective layer on the surface of the steel bar;

[0082] The process parameters of electrodeposition control are: cathode current density is 0.8A / m 2 , the deposition time is 90 min, the seawater temperature is 25°C, and the power supply voltage is 20 V;

[0083] The distance between the steel bar and the anode material is 8 cm;

[0084] The anode material is graphite;

[0085] S4, removing chloride ions: taking out the steel bars after the electrodeposition treatment and placing them in water without chloride ions, placing an anode material in the water, and connecting the steel bars and the anode material to the negative electrode and the positive electrode of the power supply respectively to remove ions on the surface of the steel bars;

[0086] The controlled process parameters are: cathode current density is 1.5A / m 2 , time is 30min, power supply voltage is 30V, distance between steel bar and anode material is 8cm, anode material is graphite;

[0087] S5. Drying: Take out the steel bars and dry them at a drying temperature of 50°C for 15 minutes.

[0088] Performance Testing

[0089] Figure 1 The surface morphology of the steel bar before electrodeposition treatment and after treatment according to the method of Example 1. Figure 1Seawater electrodeposition represents the surface morphology of the steel bar after cathode electrodeposition in step S3 in Example 1, and seawater electrodeposition + dechlorination treatment represents the final surface morphology of the steel bar according to the method in Example 1.

[0090] from Figure 1 It can be seen that the surface of the steel bar is smooth and shiny before electrodeposition treatment, and an inorganic salt-colloidal sediment protective layer is formed on the surface of the steel bar after seawater electrodeposition treatment, and the protective layer has a rough texture; and the surface of the steel bar treated with seawater electrodeposition + dechlorination also has an inorganic salt-colloidal sediment protective layer, which is no significantly different from the protective layer of the steel bar treated with seawater electrodeposition.

[0091] Figure 2 It shows the surface microscopic morphology of the steel bars that have not been treated with electrodeposition and the steel bars treated according to the method of Example 1 after being placed in a salt spray environment (ambient temperature is (35±2)°C, relative humidity is greater than 95%, and salt spray mass concentration is 5%±1%) for 7 days.

[0092] Figure 2 The non-electrodeposition treatment refers to the surface microscopic morphology of the steel bars that have not been subjected to electrodeposition treatment after being placed in a salt spray environment for 7 days; the seawater electrodeposition refers to the surface microscopic morphology of the steel bars after being placed in a salt spray environment for 7 days after the cathode electrodeposition in step S3 in Example 1; the seawater electrodeposition + dechlorination treatment refers to the surface microscopic morphology of the steel bars after being placed in a salt spray environment for 7 days according to the method in Example 1.

[0093] from Figure 2 It can be seen that after being placed in a salt spray environment, a large area of ​​rust appeared on the surface of the steel bar that was not treated with electrodeposition, while only a small area of ​​rust appeared on the surface of the steel bar treated with seawater electrodeposition, and no obvious rust occurred on the surface of the steel bar treated with seawater electrodeposition + dechlorination. The test results show that the steel bar treated with seawater electrodeposition + dechlorination has the best salt spray corrosion resistance, followed by the steel bar treated with seawater electrodeposition, and the steel bar not treated with electrodeposition has the worst performance.

[0094] Figure 3 is the linear polarization curve of the steel bar before electrodeposition treatment.

[0095] Figure 4 is the linear polarization curve of the steel bar after being treated according to the method in Example 1.

[0096] Among them, the polarization curve test method is to use an electrochemical workstation with a three-electrode system for testing, with a scanning range of ±10mV, a scanning frequency of 0.1mV / s, the working electrode is the steel bar before electrodeposition treatment or the steel bar treated according to the method in Example 1, the reference electrode is a saturated calomel electrode, and the counter electrode is a stainless steel sheet.

[0097] from Figure 3It can be seen that the self-corrosion potential of the steel bar before electrodeposition treatment is about -0.665V; Figure 4 It can be seen that the self-corrosion potential of the steel bar after treatment according to the method in Example 1 is about -0.543 V. Compared with the electrodeposition treatment, the self-corrosion potential of the steel bar treated according to the method in Example 1 becomes higher, which shows that the method of the present invention can greatly improve the corrosion resistance of the steel bar.

[0098] It can be understood that the technical features of the above-described embodiments can be arbitrarily combined. In order to make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0099] The above are only preferred embodiments of the present application, and only specifically describe the technical principles of the present application. These descriptions are only for explaining the principles of the present application and cannot be interpreted as limiting the scope of protection of the present application in any way. Based on the explanation here, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application, and other specific implementation methods of the present application that can be associated with the technicians in this field without creative work, should be included in the scope of protection of the present application.

Claims

1. An electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater. It is characterized in that The following steps are involved: The steel bar is placed in the seawater, and an anode material is placed in the seawater; The steel bar and the anode material are connected to the negative electrode and the positive electrode of the power source respectively to perform electrodeposition to form a protective layer on the surface of the steel bar; The steel bar after the electrodeposition treatment is taken out and placed in water without chloride ions, and an anode material is placed in the water at the same time, and the steel bar and the anode material are connected to the negative electrode and the positive electrode of the power supply respectively to remove the ions on the surface of the steel bar; Remove the steel bars and dry them.

2. The electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater as claimed in claim 1, It is characterized in that The seawater includes ions of the following concentrations: chloride ions 18995-191452 mg / L, sodium ions 10589-10652 mg / L, sulfate ions 2665-2677 mg / L, magnesium ions 1288-1328 mg / L, calcium ions 411-452 mg / L, potassium ions 398-401 mg / L, and zinc ions 0.024-0.025 mg / L.

3. The electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater as claimed in claim 1, It is characterized in that The steel bar and the anode material are connected to the negative electrode and the positive electrode of the power supply respectively, and the process parameters of the electrodeposition control are: the cathode current density is 0.75~5A / m 2 , the deposition time is 50min~24h, the temperature of the inorganic salt solution is 20~30℃, and the maximum power supply voltage does not exceed 50V.

4. The electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater as claimed in claim 1, It is characterized in that The steel bar after electrodeposition treatment is taken out and placed in water without chloride ions. At the same time, an anode material is placed in the water. The steel bar and the anode material are connected to the negative electrode and the positive electrode of the power supply respectively to remove the ions on the surface of the steel bar. The controlled process parameters are: cathode current density is 0.25-2A / m 2 , time is 5 to 30 minutes, and the maximum power supply voltage does not exceed 30V.

5. The electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater as claimed in claim 1, It is characterized in that Before placing the steel bars in the seawater, the seawater is filtered to remove suspended matter.

6. The electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater as claimed in claim 5, It is characterized in that Before placing the steel bars in seawater, the steel bars are pre-treated, and the pre-treatment includes: degreasing, pickling, water washing, and sandblasting the steel bars in sequence for use.

7. The electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater as claimed in claim 6, It is characterized in that The degreasing is specifically: The steel bar is placed in an alkali solution and ultrasonically treated at 30-50°C; And / or, the pickling is specifically: The degreased steel bars are immersed in a hydrochloric acid solution with a concentration of 0.1 to 0.2 mol / L for 5 to 20 minutes.

8. The electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater as claimed in claim 7, It is characterized in that The alkali solution includes at least one of a sodium hydroxide solution, a sodium carbonate solution, a sodium phosphate solution, and a sodium silicate solution; The mass concentration of the alkali solution is 2 to 10%; The ultrasonic treatment time is 10 to 20 minutes; Filtering the seawater to remove suspended matter in the seawater specifically includes filtering the seawater using a quartz sand filter, an activated carbon filter, or an ultrafiltration membrane filter.

9. The electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater as claimed in claim 1, It is characterized in that In the steps of placing the steel bar in seawater and placing an anode material in the seawater, and taking out the steel bar after the electrodeposition treatment and placing it in water without chloride ions and placing the anode material in the water, the distance between the steel bar and the anode material is 5 to 10 cm; The anode material includes at least one of graphite and stainless steel.

10. The electrochemical treatment method for improving the corrosion resistance of steel bars in concrete using seawater as claimed in claim 1, It is characterized in that In the step of taking out the steel bars and drying them, the drying temperature is 30 to 50° C. and the drying time is 15 to 60 minutes.